Pedagogia da mímesis no ensino de Filosofia: Repensando a prática educativa na educação básica - ARRUDA FILHO, Zeabel de (2021)
In this investigative work we intend to examine the proposal of employment of mimesis as a methodological resource to the teaching of philosophy in the final years of elementary school, specifically, in the class of the eighth (8th) year A, of the school Unidade Integrada Manoel Campos Sousa - annex. The challenge that we encounter when teaching philosophy at this school institution concerns the way of teaching and learning it today. We observe that the philosophical teaching-learning process results from an educational practice that is also carried out in the same way as traditional pedagogy. This finding reinforces, it seems, the idea that this pedagogical trend is becoming obsolete in the face of the needs of students and the school as it does not keep pace with social changes, thus provoking the manifestation of a passive posture of a large part of students in relation to the content proposed by the teacher. It is in this context that we are prepared to think philosophically and theoretically-methodologically the teaching of philosophy from the mimetic activity, as a way to reframe this way of teaching and learning philosophy in basic education. Therefore, this research begins with the study of the Aristotelian categories of mimesis and education, as well as the relationship between them¹. Then, we discuss the process of teaching and learning philosophy in basic education with theoretical contributions from some philosophers and educators, among which we highlight: Geraldo B. Horn (2009), Maurice Tardif (2014) and Jacques Rancière (2004). Given the hypothesis that mimesis as a foundation of poetic art contributes to the teaching of philosophy and to the critical and creative development of students in the final years of elementary school, we are engaged in proposing a didactic sequence based on mimetic activity in order to understand the result of this pedagogical-philosophical experience in the classroom. Regarding the methodology, this researchis of a qualitative nature and addresses the area of human sciences, observing the hypothetical-deductive approach method. Regarding methodological procedures, we opted for philosophical-pedagogical intervention due to the occurrence of activities aimed at the philosophical teaching learning process in the classroom, using specific data collection techniques that involve the following instruments, namely: pre-intervention semi-structured questionnaire, post-intervention structured questionnaire and socioeconomic and ethnic racial questionnaire, with a view to establishing new didactic-pedagogical strategies aimed at teaching philosophy. In theanalysis and interpretation of data, we prefer the sample description through visual elements (tables, graphs, lists and diagrams) with explanatory notes that aim at clarifying the information obtained. Ahead, we try to compare the data collected in thisresearch with the hypothesis constructed in order to prove the veracity of the assumption and, thus, recognize it as a valid answer to the investigated problem.